Die Künstleretiketten von Nittardi. - Canali, Stefania; Dohm, Horst; Femfert, Peter; Schröder, Thomas (Frankfurt am Main : Dott. Stefania Canali, 2001)
Bruni, Bruno ; Minuzzi, Maurilio ; Korab, Karl ; Dittrich, Simon ; Berrocal, Miguel ; Hrdlicka, Alfred ; Wunderlich, Paul ; Hausner, Rudolf ; Hundertwasser ; Janssen, Horst ; Adami, Valerio ; Corneille ; Penck, A.R. ; Arroyo, Eduardo ; Waydelich, Raymond ; Veronesi, Luigi ; Mitoraj, Igor ; Bach, Elvira ; Tadini, Emilio ; Brandeis Crawford, Sandra
boek